Orchids Diversity in the Sicikeh-Cikeh Forest, North Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Hartini S. 2019. Orchids Diversity in the Sicikeh-Cikeh Forest, North Sumatra, Indonesia. Biodiversitas 20: 1087-1096. Sicikeh-cikeh forest includes three forest areas, namely Adian Tinjoan Customary Forest, Adian Tinjoan Protection Forest, and Taman Wisata Alam Sicikeh-cikeh. Typical vegetation of this area is mountain forest with large diversity of plant species. Among the species, orchid is one of the potential plants found diversely in this location and has not yet been recorded. The exploration activities were conducted at Sicikeh-cikeh forest. Orchid exploration was conducted to collect living plants for ex situ conservation purpose. Orchid inventory, to record orchid diversity in this area, was based on plant collection by purposive random sampling. The results of the study recorded approximately 102 different species from 30 genera of orchids in this area. Typical epiphytic and terrestrial highland orchids were found and very common in Sumatra. Among the species found are endemic Sumatra, such as Coelogyne brachygyne, Coelogyne salmonicolor, Dendrobium kruiense, Epigeneium pulchellum, Thrixspermum gombakense, Corybas stenotribonos and Paphiopedilum tonsum. Interesting terrestrial orchids include Kuhlhasseltia javanica, Neuwiedia zollingeri var. javanica, Paphiopedilum tonsum, Phaius callosus, Corybas stenotribonos, Calanthe aurantiaca, Calanthe chrysoglossoides, and Calanthe pulchra. While interesting epiphytic orchids include Bulbophyllum absconditum, Bulbophyllum coloriferum, Coelogyne brachygyne, Epigenium pulchellum, Eria bractescens, Eria pachystachya, Pholidota gibbosa, and Thrixspermum amplexicaule.